A Portrait of our Times : An Introduction to the Logan Collection. - Garrels, Gary; Ross, David A. (San Francisco : San Francisco Museum of Modern Art, 1998)
Clemente, Francesco ; Colescott, Robert ; Dumas, Marlene ; Fang Lijun ; Gilbert & George ; Gormley, Antony ; Guston, Philip ; Hamilton, Richard ; Hirst, Damien ; Kiefer, Anselm ; Koons, Jeff ; Ligon, Glenn ; Liu Wei ; Morimura, Yasumasa ; Muñoz, Juan ; Nauman, Bruce ; Patterson, Richard ; Quinn, Marc ; Richter, Gerhard ; Ruscha, Ed ; Schütte, Thomas ; Sherman, Cindy ; Warhol, Andy ; Yuskavage, Lisa
A Portrait of our Times : An Introduction to the Logan Collection, San Francisco Museum of Modern Art, San Francisco, September 29, 1998 - January 03, 1999
Engels
boek